Normative values of pattern reversal visual evoked potentials in adult population of Mewat region, North India - Kaushik, Navneet K.; Jaiswal, Abhishek K.; Kumar, Anil (International Journal of Research in Medical Sciences, 2025)
Background: Visual evoked potentials (VEPs) are a sensitive neurodiagnostic tool used to evaluate the functional integrity of visual pathways non-invasively. The present research was aimed at establishing the normative values of the VEP parameters among healthy adults in Mewat region, North India. Methods: This cross-sectional study was conducted on 130 healthy adults, 91(70%) males and 39 (30%) females, in the age group of 18 to 60 years. Single channel recording was done using transient pattern (checkerboard) reversal stimuli (check size 13”) presented at a reversal rate of 1 Hz. A total of 100 responses were recorded twice monocularly in each subject. Results: We observed P100 latency of 103.77±5.74 msec (right eye), 102.88±5.14 msec (left eye) for males and 98.80±6.59 msec (right eye), 98.09±5.54 msec (left eye) for females. P100 latency was significantly longer in males than females (p<0.001). N75-P100 amplitude was 5.61±2.74 µV (right eye), 5.73±3.06 µV (left eye) in males and 5.53±2.86 µV (right eye), 5.50±3.24 µV (left eye) in females. P100 amplitude was comparable between the two sexes. Conclusions: Gender based reference values of P100 latency and N75-P100 amplitude for the regional population were established. P100 latency was comparable to the values reported in most of the previous studies; however, reported N75-P100 amplitude was significantly lower which might be due to variation in technical factors.